2023
DOI: 10.3389/fnut.2023.1008971
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a short nutrition literacy scale for young adults

Abstract: BackgroundDue to their high media use, young adults are frequently exposed to contradictory or even erroneous nutrition information. To properly handle and critically assess nutrition information, young adults (both general population and patient populations) need adequate levels of nutrition literacy. Currently there is a lack of suitable instruments to measure nutrition literacy in young adults (18–25 years). Therefore the aim of this study was to develop and validate a Short Nutrition Literacy (S-NutLit) sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…Concerning the model fit, it is shown that all the indicators had an excellent estimation, and only the RMSEA indicator was at an acceptable level of 0.063 [58] (see Table 5, Figure 1). Due to previous evidence by Vrinten et al [20] and the exploratory factor analysis performed (Table 3), a two-factor internal structure was considered for the confirmatory factor analysis (model 1). However, to verify the fit of the model, a unidimensional analysis of the 11 factors was performed to explain a single factor (model 2), and it was found that the model with a single factor did not achieve a good fit, so the initial model (model 1) with two factors was considered the most appropriate for the S-NutLit scale.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning the model fit, it is shown that all the indicators had an excellent estimation, and only the RMSEA indicator was at an acceptable level of 0.063 [58] (see Table 5, Figure 1). Due to previous evidence by Vrinten et al [20] and the exploratory factor analysis performed (Table 3), a two-factor internal structure was considered for the confirmatory factor analysis (model 1). However, to verify the fit of the model, a unidimensional analysis of the 11 factors was performed to explain a single factor (model 2), and it was found that the model with a single factor did not achieve a good fit, so the initial model (model 1) with two factors was considered the most appropriate for the S-NutLit scale.…”
Section: Resultsmentioning
confidence: 99%
“…Studies indicate that in nutritional literacy, the information skills and expert skills are essential to ensure that people can access, understand, and use accurate and relevant nutritional information. Vrinten et al [ 20 ] states that information skills refer to the ability to find, evaluate, and use information effectively. In the context of nutritional literacy, these skills are essential for people to make informed decisions about their dietary choices and overall health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the Nutritional Literacy (NL) variable, this study applied the short 11-item scale developed by Vrinten et al ( 120 ). To evaluate the variables of the theory of planned behavior, adaptation was proposed by Kumar et al ( 121 ), where Attitude, Subjective Norm, and Perceived Behavioral Control have three items each, and the willingness to consume foods from healthy brands has seven items ( Appendix B ).…”
Section: Methodsmentioning
confidence: 99%
“…Generally, Nutritional Literacy is de ned as an individual's capacity to acquire, process, and comprehend basic information and skills necessary for making appropriate nutritional decisions [10][11][12]. On the other hand, NL can also be de ned as the extent to which individuals are capable of acquiring, understanding, and accepting fundamental concepts and information related to nutrition [13]. Therefore, it is essential to assess the level of NL among healthcare professionals in order to provide necessary counseling and education in this regard.…”
Section: Introductionmentioning
confidence: 99%